2021
DOI: 10.1007/s00203-021-02305-7
|View full text |Cite
|
Sign up to set email alerts
|

Marivivens aquimaris sp. nov., isolated from seawater

Abstract: A Gram-stain-negative, strictly aerobic, non-agellated, rod-shaped bacterium, designated GSB7 T , was isolated from seawater collected at the Yellow Sea coast of South Korea. Catalase and oxidase activities were positive. Growth occurred at pH 6.0-9.0 (optimum pH 7.0), 10-40 °C (optimum 30 °C) and with 0-8% NaCl (optimum 1-2%). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain GSB7 T belonged to the genus Marivivens, showing the sequence similarities of 96.3, 96.1, and 96.0% with Mari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The genus Paradonghicola was also effectively published based on a single species [2] and validly published in 2019. The genus Marivivens was effectively published based on a single species [3] [4] and 'Marivivens aquimaris ' Kim et al 2021 [5]. Phylogeny of 16S rRNA gene sequences found that A. zhoushanense G7 T and P. geojensis FJ12 T were closely related to M. donghaensis AM-4 T .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Paradonghicola was also effectively published based on a single species [2] and validly published in 2019. The genus Marivivens was effectively published based on a single species [3] [4] and 'Marivivens aquimaris ' Kim et al 2021 [5]. Phylogeny of 16S rRNA gene sequences found that A. zhoushanense G7 T and P. geojensis FJ12 T were closely related to M. donghaensis AM-4 T .…”
Section: Introductionmentioning
confidence: 99%
“…2018 [4] and ‘ Marivivens aquimaris ’ Kim et al . 2021 [5]. Phylogeny of 16S rRNA gene sequences found that A.…”
Section: Introductionmentioning
confidence: 99%